The biopolitics of violence: Instances of Anti-Semitism in interwar Romania - Panu, Mihai Adrian (Journal of Education Culture and Society, 2020)
The primacy of totalitarian ideologies in interwar Europe represents even nowadays a major historiographical challenge due to its multicausal character and various forms of appearance. This paper attempts to analyze the anti-Semitic phenomenon in interwar Romania primarily by taking into account its determinant factors. We assume that the emergence of radical ideologies in Central and Eastern Europe can optimally be understood if both regional and systemic causes are properly highlighted. The regional causes include local societal predispositions, ethno-cultural cleavages and specific political movements. On the other hand the systemic causes imply predominantly geopolitical factors and the repartition of power in the international system. Moreover we assume that the emergence and manifestations of extremism can be considered a direct result of political disputes between ethno-cultural groups which were systematically exposed to ideological and propaganda pressure.